The Complexity of Metaphor Translation. A Case Study - Loredana PUNGĂ; Marius GOLEA (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2022)
This paper is a case study of metaphor translation. It focuses on the translation techniques used to render some of the metaphors in Oscar Wilde’s “The Picture of Dorian Grey” into Romanian. The actual case study follows after a brief overview of approaches to metaphor in general and to metaphor translation in particular. The conclusion indicates that there is a diversity of translation techniques that have been used, most of them not based on word-for-word equivalences.